Investigations of the Microvasculature of the Human Macula Utricle in Meniere’s Disease - Ishiyama, Gail; Lopez, Ivan A.; Acuna, Dora; Ishiyama, Akira (Frontiers in Cellular Neuroscience, 2019)
The integrity and permeability of the blood labyrinthine barrier (BLB) in the inner ear is important to maintain adequate blood supply, and to control the passage of fluids, molecules and ions. Identifying the cellular and structural components of the BLB, the vascular endothelial cells (VECs), pericytes, and the perivascular basement membrane, is critical to understand the pathophysiology of the inner ear microvasculature and to design efficient delivery of therapeutics across the BLB. A recent study of the normal and pathological ultrastructural changes in the human macula utricle microvasculature demonstrated that the VECs are damaged in Meniere’s disease (MD), and further studies identified oxidative stress markers (iNOS and nitrotyrosine) in the VECs. Using fluorescence microscopy, the microvasculature was studied in the macula utricle of patients diagnosed with MD that required transmastoid labyrinthectomy for intractable vertigo (n=5), and patients who required a translabyrinthine approach for vestibular schwannoma (VS) resection (n=3). Normal utricles (controls) were also included (n=3). VECs were identified using rabbit polyclonal antibodies against the glucose transporter-1 (GLUT-1) and pericytes were identified using mouse monoclonal antibodies against alpha-smooth muscle actin (α-SMA). Immunofluorescence (IF) staining was made in half of the utricle and flat mounted. The other half was used to study the integrity of the BLB using transmission electron microscopy. GLUT-1-IF, allowed delineation of the macula utricle microvasculature (located in the stroma underneath the sensory epithelia) in both MD and VS specimens. Three sizes of vessels were present in the utricle vasculature: Small size (<15 m), medium size (15 to 25 m) and large size >25 m. α-SMA-IF was present in pericytes that surround the VECS in medium and thick size vessels. Thin size vessels showed almost no α-SMA-IF. AngioTool software was used for quantitative analysis. A significant decreased number of junctions, total vessel length, and average vessel length was detected in the microvasculature in MD specimens compared with VS and control specimens. The deeper understanding of the anatomy of the BLB in the human vestibular periphery and its pathological changes in disease will enable the development of non-invasive delivery strategy for the treatment of hearing and balance disorders.